Chronic lymphocytic leukemia in a farmer and vegetable seller: Associated with exposure of multiple work-related hazards? - Dewi S. Soemarko; firly ratsmita (School of Medicine, Universitas Syiah Kuala, 2021)
There are several risk factors associated with the incidence of chronic lymphocytic leukaemia (CLL), namely genetic factors, smoking, and occupational exposure to chemicals. We highlight a possible association of a CLL case and the occupational. We reported a case of CLL patient, a 69-year-old man, who had been working as a vegetable seller and a chili farmer since 15 and 4 years ago, respectively. The patient was diagnosed with CLL three months prior to admission and had a history of three times blood transfusions. The patient only complained of paleness and weakness without any specific symptoms. No swelling of the lymph nodes, hepatomegaly, or splenomegaly was found. As a vegetable seller and chili farmer, the patient was exposed to five hazards, physical, chemical, biological, ergonomic to psychosocial. Therefore, it is necessary to analyse whether there was an association between the patient's work and the current CLL. To diagnose occupational diseases, several steps are needed. In this patient, one of the risk factors that could lead to CLL was exposure to chemicals such as pesticides. However, information regarding the content of pesticides used was unclear and there were no results obtained from pesticides biomarker examination that might cause the disease, making it difficult to establish a definitive diagnosis of work-related cause. The patient could be advised to have biomarkers of pesticide substances checked, which requires control of farmers and vegetable sellers who might have been exposed to pesticides. The control mechanism might be started from elimination, substitution, engineering, administration, and use of personal protective equipment. A control mechanism is necessary to prevent the entry of contaminants into the body, especially through inhalation, oral, and dermal pathways. It is recommended to examine for biomarkers of pesticides containing organophosphates, organochlorines, or carbamates to determine the chronic effects on the accumulation of these chemicals that might cause CLL.